Dismal science and medicine embrace. (18th January 2018) - Thorp, John
Abstract : Deputy Editor‐in‐Chief, Dr John Thorp, discusses his top article from this issue in an audio podcast available at:https://soundcloud.com/bjog/February-editors-choice-2018